Efek Pemberian α-Mangostin Dari Garcinia tetranda Pierre Terhadap Morfologi P.Falciparum (Journal of Tropical Pharmacy and Chemistry, 2025)
Morphological changes assay to P. falciparum from the effects of Î±-mangostin from G. tetranda using TEM methods has been done. This test aims to determine the effect of mangostin on P. falciparum by observing morphological ultrastructure of P. falciparum using transmission electron microscope (TEM). Î±-Mangostin known to cause morphological changes in ultrastructure of P.falciparum after contact with Î±- mangostin on the 12 and 24 hour.